Papulopustular lesions of the face caused by panitumumab: case report and literature review - Ravasco Jonathan; Lebaud Philippe; Bodin Hélène (EDP Sciences, 2018)
Introduction: Panitumumab (VECTIBIX®) is a monoclonal antibody used alone or in combination with a chemotherapy for management of metastatic colorectal cancer. Observation: A patient treated with this protocol manifested skin lesions; the etiological diagnosis was difficult. The lesions, namely a papulopustular rash at the lower third of the face, and the medical history allowed to diagnose an acute skin toxicity case due to this monoclonal antibody. Commentary: Many side effects are related to the panitumumab, among which dermatologic adverse events having already been the subject of some publications. Nevertheless, several studies conclude that the therapeutic benefit of this epidermal growth factor receptor inhibitor makes acceptable these complications. Conclusion: Stop treatment and corticosteroids allowed a whole and quick disappearance of skin lesions. Alongside dermatologists and infectious diseases specialists, the opinion of an oral surgeon was useful to provide an answer to these symptoms.